The Relationship between Renewable Energy Consumption, CO2 Emissions, Economic Growth, and Industrial Production Index: The Case of Kazakhstan - Issayeva, Gulmira; Dyussembekova, Zhanar; Aidarova, Aina B.; Makhatova, Adelina B.; Lukhmanova, Gulnar; Absemetova, Dariya; Bolganbayev, Artur (International Journal of Energy Economics and Policy, 2023)
CO2 emission is an important parameter that indicates a country’s development level and respect for nature. It’s a well-known fact that a country’s industrialization level and economic growth have a direct impact on CO2 emissions. We must prioritize the use of energy obtained from renewable sources and be mindful of our impact on the environment. This study analyses the industrial production index, economic growth, and the percentage of energy produced from renewable energy sources in energy consumption and CO2 emissions in Kazakhstan. The data are collected from the National Statistical Bureau of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan, Our World in Data, and the World Bank web pages. Research data were analyzed using the Johansen cointegration test, Vector Autoregressive (VAR) analysis, Granger causality analysis, and VECM model. In the study, we analyzed three key factors that impact CO2 emissions in Kazakhstan. Our findings revealed that these factors account for 16.1% of the variability in CO2 emissions, indicating the statistical accuracy of these variables. When deciding on renewable energy investments, it is very important to determine the causal relationship between renewable energy consumption and CO2 emissions. It seems that industrial development and economic growth can occur without any major concerns about CO2 emissions. This is based on the lack of statistical significance in the relationship between CO2 emissions and both the industrial production index and economic growth.